Keterampilan Pengisian Partograf pada Mahasiswa Akademi Kebidanan di Wilayah Kota Jakarta Timur tahun 2015 - Aan Rosanti; Sutopo Patria Jati; Syamsulhuda Budi Mustofa (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: Partographs an observation management guidelines and normal deliveries which will facilitate birth attendants in detecting emergency cases in the mother and fetus. Partographs plays an important role in determining the diagnosis of labor.Method: This type of research is observational cross-sectional design. Data obtained from the source using observation sheets and questionnaires. The location of this study Midwifery Academy campus located in East Jakarta. Subjects were all students who have already studied partograf and aid delivery practices, the number of samples 201 student midwives based on inclusion criteria. Analysis of the results using the chi square test and multiple logistic regression.Results: The results showed good skills partograf use (56.7%), most of the students age ≥ 20 years (58.7%), high student motivation (57.7%), students' perceptions of the learning process both (52.2%) , students' perceptions of good pendidian facilities (52.75). The relationship between student motivation (p = 0.005) with the charging partograf skills and no correlation between age, the perception of the learning process and perceptions of educational facilities with charging partograf skills. Results of regression test showed the influence of motivation by charging partograf (p value = 0.004, ß exp 2,350). Recommendations from this study for all student midwives who practice in the delivery room must use partoraf in every delivery assistance. For midwifery institutions to enhance cooperation with land CI practice in providing guidance and monitoring the delivery report students.Keywords: Skills filling partograf, motivation, learning, education facilities.